2015
DOI: 10.1155/2015/498304
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Organic Dyes by TiO2@Yeast‐Carbon Composite Microspheres and Their In Situ Regeneration Evaluation

Abstract: TiO2@yeast-carbon microspheres with raspberry-like morphology were fabricated based on the pyrolysis method. The obtained products were characterized by field emission scanning electron microscopy (FE-SEM), energy dispersive spectrometry (EDS), and X-ray diffraction (XRD). Effects of initial dye concentration and contact time on adsorption capacity of TiO2@yeast-carbon for cationic dye methylene blue (MB) and anionic dye congo red (CR) were investigated. Experimental data were described by Langmuir, Freundlich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…As combined form of Langmuir and Freundlich models, the Koble-Corrigan isotherm can better fit the experimental data for both low and high solute concentrations [33]. This model is used for heterogeneous adsorption surfaces and is transformed to Langmuir isotherm when n = 1 [54]. The n values at 288 and 308 K suggested an adsorption reaction stoichiometry of more than 1 solute molecule per free sorbent binding site [55].…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…As combined form of Langmuir and Freundlich models, the Koble-Corrigan isotherm can better fit the experimental data for both low and high solute concentrations [33]. This model is used for heterogeneous adsorption surfaces and is transformed to Langmuir isotherm when n = 1 [54]. The n values at 288 and 308 K suggested an adsorption reaction stoichiometry of more than 1 solute molecule per free sorbent binding site [55].…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…Figures d and S8 exhibit the emission maximum as a function of the dye concentration of the Rh@bio-MOF-1 composites. The relationship between the dye concentration and the emission peak can be well-fitted by using Koble–Corrigan equation wherein C e refers to the dye concentration, Q e refers to the emission peak wavelength, and A KC , B KC , and n are Koble–Corrigan isotherm constants. According to eq , the Rh@bio-MOF-1 composites with a very broad range of emission wavelengths can be obtained easily by formulating a dye impregnation solution with a corresponding concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it could be observed that the estimated q e values were in line with the experimental ones in contrast to the PFO and Elovich models. These findings suggest that one of the rate-determining steps could be chemical sorption, implying valence forces via electron exchanges or shares [73].…”
Section: Adsorption Kinetics Studiesmentioning
confidence: 90%